INTERACTIVE M-LEARNING MEDIA BASED ON SMART APPS CREATOR OF ENGLISH GRAMMAR - Kholifuddin Roma; Segu, Segu; Zarkasi, Zarkasi; Alfiandri, Sandi (Program Studi Tadris Bahasa Inggris Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2024)
This study aims to produce an interactive M-learning media design based on Smart Apps Creator for the teaching and learning process, particularly the Simple Past Tense, through validity, practicality, and effectiveness. It is a development study with a 4-D design, Define, Design, Develop, and Disseminate, but this study only did at the development stage. The subjects of this study are eighth-grade students of SMP Awaluddin Kubu Raya and three validators as three experts, material and media experts, and field trial subjects. The data collection techniques used are indirect communication techniques and measurement techniques. The data collection tools used included validation sheets, which consist of media validation sheets and tests. The study results conclude that the interactive M-learning media design based on Smart Apps Creator for teaching English on Simple Past Tense material at SMP VIII Awaluddin Kubu Raya was categorized as very valid, practical, and effective. Therefore, it is hoped that this app will be used in the English teaching process.